TOROS optical follow-up of the advanced LIGO–VIRGO O2 second observational campaign. Issue 2 (3rd January 2020) - Artola, Rodolfo; Beroiz, Martin; Cabral, Juan; Camuccio, Richard; Castillo, Moises; Chavushyan, Vahram; Colazo, Carlos; Cuevas, Hector; DePoy, Darren L; Díaz, Mario C; Domínguez, Mariano; Dultzin, Deborah; et al.
ABSTRACT: We present the methods and results of the optical follow-up, conducted by the Transient Optical Robotic Observatory of the South Collaboration, of gravitational wave events detected during the Advanced LIGO–Virgo second observing run (2016 November–2017 August). Given the limited field of view (∼100 arcmin) of our observational instrumentation, we targeted galaxies within the area of high localization probability that were observable from our sites. We analysed the observations using difference imaging, followed by a random forest algorithm to discriminate between real and spurious transients. Our observations were conducted using telescopes at Estación Astrofísica de Bosque Alegre, Cerro Tololo Inter-American Observatory, the Dr. Cristina V. Torres Memorial Astronomical Observatory, and an observing station in Salta, Argentina.